2004
DOI: 10.1164/rccm.200404-519oc
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep-disordered Breathing in Middle-aged Korean Men and Women

Abstract: With many epidemiologic studies made to establish the prevalence of sleep-disordered breathing (SDB) and obstructive sleep apnea syndrome (OSAS) in Western countries, no such data have been reported in Korea. The purpose of this study was to examine the prevalence of SDB and OSAS, and their related factors in Korean adults aged 40-69 years. Among the total of 5,020 participants at the baseline examination of the Korean Health and Genome Study, a random sample of 457 men and women was studied with employment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
256
8
18

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(306 citation statements)
references
References 48 publications
24
256
8
18
Order By: Relevance
“…These strongly positive associations of BMI and BMI changes since the age of 20 with SDB were consistent with the results of previous studies, but this study provided further evidence that long-term changes in BMI are associated with SDB. 10,[12][13][14] In our study, 55% of the men with RDI X10 had BMI X25, which is similar to findings for the USA, where 58% of Americans with AHI X15 had BMI X25. 1 A 10% increase in weight over 4 years was associated with a six times higher risk of AHI X15 3 and a weight gain of X5 kg over 5 years with a three times higher risk of AHI X15 18 in follow-up studies of Americans.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These strongly positive associations of BMI and BMI changes since the age of 20 with SDB were consistent with the results of previous studies, but this study provided further evidence that long-term changes in BMI are associated with SDB. 10,[12][13][14] In our study, 55% of the men with RDI X10 had BMI X25, which is similar to findings for the USA, where 58% of Americans with AHI X15 had BMI X25. 1 A 10% increase in weight over 4 years was associated with a six times higher risk of AHI X15 3 and a weight gain of X5 kg over 5 years with a three times higher risk of AHI X15 18 in follow-up studies of Americans.…”
Section: Discussionsupporting
confidence: 88%
“…7 The prevalence of SDB (apnea-hypopnea index (AHI), X15) was 9-14% for western adult men [8][9][10] and 5-10% for their Asian counterparts. 11,12 We previously reported that SDB was positively associated with overweight and excessive daytime sleepiness among Japanese adults. 13,14 To date, however, no data have been available on the association of weight change with SDB and excessive daytime sleepiness for Asian populations.…”
Section: Introductionmentioning
confidence: 98%
“…(10) The definition of OSAS is an apnea-hypopnea index (AHI) above five events per hour of sleep, together with excessive daytime sleepiness. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) A recent epidemiological study conducted in the city of São Paulo, Brazil, (11) showed a high prevalence of OSAS in the adult population (32.8%). (12) In that study, OSAS was defined according to the criteria of the most recent International Classification of Sleep Disorders, published by the American Academy of Sleep Medicine (AASM) in 2005, (13) which state that a diagnosis of OSAS can be confirmed if the subject has an AHI of 5.0-14.9 events per hour of sleep and presents with at least one of the following complaints: loud snoring, excessive daytime sleepiness, and fatigue.…”
Section: Introductionmentioning
confidence: 98%
“…Obstructive sleep apnea syndrome (OSAS) is a highly prevalent condition that is observed in 1.2% to 7.5% of the general population, (1)(2)(3)(4)(5)(6)(7)(8)(9) mostly in adults and primarily in obese males. (10) The definition of OSAS is an apnea-hypopnea index (AHI) above five events per hour of sleep, together with excessive daytime sleepiness.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is one of the most common sleep disturbances; it affects 3.2-20 % of the adult population [1,2] and has a negative impact on public health, increasing both morbidity and mortality [3]. Although continuous positive airway pressure (CPAP), oral appliances, and surgical modifications of the airway are considered parts of the routine management of patients with OSA, there remain many problems with these treatments in practice.…”
Section: Introductionmentioning
confidence: 99%